MICROBIOLOGICAL ANALYSIS AND ASSESSMENT OF COASTAL BATHING WATERS IN REGION VARNA - Gabriela Tsankova; Eliyana Ivanova; Rumen Konstantinov; Tatina Todorova; Neli Ermenlieva (Peytchinski Publishing, 2018)
Water contaminated by human and animal excreta may contain a range of pathogenic microorganisms such as viruses, bacteria and protozoa. During the bathing season, water samples are taken and analyzed for Escherichia coli and intestinal enterococci. The aim of these study is to assess the quality of bathing waters along Black Sea Coast in Varna Region from 2012 to 2016. Materials and Methods: The information about microbiological monitoring of coastal bathing waters in Region Varna is received from Regional Health Inspection - Varna. Results and discussion: From May 2012 to August 2016, 1117 water samples were collected and analyzed in the Laboratory of Sanitary Microbiology of Regional Health Inspection - Varna. In the region of Varna, there is a tendency to increase the number of bathing areas with excellent water quality. In Avren Municipality, bathing water was classified as good and excellent. In Shkorpilovtsi - Tsentralen plazh, the bathing water was excellent quality. In Byala Municipality there was a deterioration in the quality of the seawater. During 2012-2016 two of these 17 sites - Riviera, located in resort Golden Sands and St. Elias located in St. St. Konstantin and Elena had excellent bathing water quality. The water indicators of Ofitserski plazh- Varna and Tsentralen plazh, Zlatni pyasatsi - PSVO were poor, while the indicators of Varna -Yuzhen plazh were satisfying or good. Conclusion: According to the European Environment Agency, the development and improvement of community water supply and collecting system will have a positive effect on the quality of bathing water.